2020
DOI: 10.5152/ejbh.2020.4984
|View full text |Cite
|
Sign up to set email alerts
|

A Case Report of Primary Breast Angiosarcoma: Clinical Presentation and Outcome After Adjuvant Radiotherapy

Abstract: European Journal of Breast Health (Eur J Breast Health) is an international, scientific, open access periodical published by independent, unbiased, and double-blinded peer-review principles. It is the official publication of the Turkish Federation of Breast Diseases Societies, and Senologic International Society is the official supporter of the journal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…A few reports have indicated the increased efficacy of radiotherapy 12 . In a case report on a patient with primary breast angiosarcoma, although the tumor size was large and the margin was positive, the patient survived with a 66‐month disease‐free period after surgery plus radiotherapy 33 . Despite the limited value of the data as a reference due to the study scale, the multidisciplinary management of the patient is notable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few reports have indicated the increased efficacy of radiotherapy 12 . In a case report on a patient with primary breast angiosarcoma, although the tumor size was large and the margin was positive, the patient survived with a 66‐month disease‐free period after surgery plus radiotherapy 33 . Despite the limited value of the data as a reference due to the study scale, the multidisciplinary management of the patient is notable.…”
Section: Discussionmentioning
confidence: 99%
“… 12 In a case report on a patient with primary breast angiosarcoma, although the tumor size was large and the margin was positive, the patient survived with a 66‐month disease‐free period after surgery plus radiotherapy. 33 Despite the limited value of the data as a reference due to the study scale, the multidisciplinary management of the patient is notable. Feinberg et al compared the survival of patients with breast angiosarcoma (radiation‐associated) treated by sarcoma service and local hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has shown that cytotoxic chemotherapies, in particular anthracycline-based regimens and taxanes can produce significant responses to therapy in a subset of patients (66). Adjuvant radiotherapy could be used to reduce the incidence of locoregional recurrence (67). However, the disease is usually resistant to currently available chemotherapy and radiotherapy, which may not alter the poor prognosis.…”
Section: Discussionmentioning
confidence: 99%